Pemanfaatan Limbah Kulit Kopi sebagai Pupuk Organik dan Hubungan dengan Produksi dan Pendapatan Petani di Desa Berasang, Kecamatan Kisam Tinggi, OKU Selatan - Dotami, Davi; Sriati, Sriati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Dotami, D., & Sriati, S. (2024). Utilization of coffee peel waste as organic fertilizer and relationship with production and farmers' income in Berasang Village, Kisam Tinggi Subdistrict, South OKU. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 609‒622). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coffee skin waste was originally considered as waste, but it contains nutrients such as nitrogen, phosphorus and potassium which are needed by plants so that it can be used as fertilizer. Research objectives: (1) identify the characteristics of coffee farmers in Berasang Village (2) to analyze the factors affecting the income of coffee farmers in Berasang Village (3) to analyze the differences in production and income of coffee farmers who use and do not use coffee skin waste as organic fertilizer. The research was conducted using survey method, the sample was taken randomly as many as 42 people from 750 population members. Research results: (1) the characteristics of coffee farmers are 23 men (54.76%) and 19 women (45.24%) with an average: age of 42 years, high school education (50%) and 26 years of farming experience (2) factors that have a significant effect on income are organic fertilizer from coffee skin waste (Sig.0.02) while those that do not significantly affect the quality of coffee beans (Sig.0.94), land area (Sig.0.33) and production costs (Sig.0.87) (3) farmers who use coffee skin waste on average: production of 1,039kg/ha, income of Rp56,217,983, and land area of 2 ha while those who do not use the average: production of 741kg/ha income of Rp40,190,482/ha, and land area of 2 ha. The T-test shows that there is a significant difference in income between coffee farmers who use and do not use coffee skin waste as organic fertilizer. It can be concluded that the use of coffee skin waste as organic fertilizer is very influential in increasing the production and income of coffee farmers in Berasang Village, Kisam Tinggi Subdistrict, OKU Selatan Regency.